PENGARUH PANDEMI COVID-19 TERHADAP PENDAPATAN PELAKU USAHA HOTSPOT (WIFI) DI DESA SUWANGI, LOMBOK TIMUR - YUSRI HAMZANI; Sofiatul Aini (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2022)
This paper discusses the effect of the pandemic on the Hotspot (wifi) business in Suwangi Village. In discussing the main loci, the researcher used two types of data; primary and secondary. Primary data was obtained through the process of observation and interviews with parties related to the main locus of research. This type of research is known as qualitative research based on field studies. After going through a long journey, the author finds that people are looking for other business opportunities as a side business, namely the wifi business. From this effort, the community can prevent the possibility of a decrease in income because selling wifi vouchers during the covid-19 pandemic can increase income because many consumers need it. The factors that affect the income of hotspot (wifi) business actors are online learning and working from home and wifi is more affordable than other networks. This makes wifi many who are interested in using it so that business actors can easily earn profits. In this case, it is not only the seller who benefits but also the consumer because to connect online the user can spend a more efficient budget.